AB0049 Appearance of CD14+CD15+ Poplulation During the Differentiation from RA-IPS Cells into Monocytes. (10th June 2014) - Nishimoto, N.; Murakami, M.; Ito, M.N.; Saito, M.; Niwa, A.; Nakahata, T.
Abstract : Background: Enhanced expression of CD14+CD15+ cells has been reported in the bone marrow of patient with severe rheumatoid arthritis (RA) (Tomita et al, J. Rheumatology, 1997). CD14+CD15+ cells (the phenotype of previously described "abnormal" myeloid cells) has been also reported to be increased in peripheral blood stem cell harvests on a per CD34+cell basis (Snowden et al, Br. J of Haematol, 1998) suggesting the abnormal process in the early differentiation of bone marrow cells in RA patients. Our study is focusing to clarify the appearance of CD14+CD15+ population in the early differentiation of bone marrow cells from RA patients. As the strategy, we utilize the monocyte differentiation system of induced pluripotent stem (iPS) cells derived from RA patients. Objectives: To examine whether the CD14+CD15+ cells appear during hematologic differentiation process of the iPS cells established from RA patients (RA-iPS). Methods: iPS cells were established from skin fibroblasts and peripheral blood mononuclear cells from RA patients as described previously. Six days after transduction, the cells were harvested and re-plated onto mitotically inactivated SNL feeder cells. For the healthy controls, non-onset family members (NOF) of the patients are recruited as donors in order to adjust hereditary background as much as possible. Monocytes were induced from each iPS clone culture on feeder-free conditions using a previously reported method (Niwa et al, PLoS One, 2011). The cells collected from each culture were stained with specified antibodies against CDs, including CD14 and CD15 and were analyzed by fluorescence-activated cell sorting (FACS) on day 12, 15, 18, 21 and 25. Results: Cultured cells started to express CD14 on the day 12 and more than 90% of the cells expressed CD14 on the day 21 in the monocyte differentiation induction course. According to the expression levels of CD14, the cell population was divided into three groups: CD14 (−), CD14 (+) and CD14 (++). CD15 (+) cells were observed in CD14 (−) and CD14 (+) population but not in CD14 (++) population. The CD15+ cells in CD14 (+) transiently appeared in RA-iPS derived cells at 11.9±2.8% (mean ± SE) on day15. However these cell proportion in NOF was1.7±2.0%. Meanwhile, CD15+ cells in CD14 (−) proportion decreased during monocyte differentiation in RA-iPS cells, but remained in NOF-iPS cells (representative data, RA 31.5, 20.6, 15.6%, NOF 47.3, 46.1, 47.3%, on day15, 18 and 21). Conclusions: We successfully differentiated iPS cells into monocytes and found CD14+CD15+cells transiently appeared only in the very early differentiation process of RA-iPS cells into monocytes. Taken together with the evidence that CD14+CD15+cells exist in RA patient bone marrow, abnormal early differentiation of myeloid/monocyte lineage cells may be pathologically involved in RA. Functional analysis will be required to elucidate the role of this distinct CD14+CD15+population in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3073